American GI Forum 1996 - San Jose Queen Coronation Rehearsal - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1996 American GI Forum - San Jose Chapter Queen Coronation rehearsal. Also includes a live dance performance (55:50).